Molecular epidemiology and antifungal susceptibility profiles of clinical Cryptococcus neoformans/Cryptococcus gattii species complex. Issue 1 (21st November 2019) - Bandalizadeh, Zainab; Shokohi, Tahereh; Badali, Hamid; Abastabar, Mahdi; Babamahmoudi, Farhang; Davoodi, Lotfolah; Mardani, Masoud; Javanian, Mostafa; Cheraghmakani, Hamed; Sepidgar, Ali Asghar; Badiee, Parisa; Khodavaisy, Sadegh; et al.
Abstract : Introduction. Limited data regarding the epidemiology and susceptibility profiles of cryptococcosis are available in the Middle East. Aim. Our study aimed to evaluate the molecular diversity, mating types and antifungal susceptibility pattern of Cryptococcus species ( n =14) isolated from 320 suspected patients with cryptococcosis. Methodology. The URA5 gene was subjected to restriction fragment length polymorphism and sequence analysis. In addition, in vitro antifungal susceptibility testing was performed by Clinical and Laboratory Standards Institute (CLSI) M27-A4 and M59 guidelines. Results. Overall, 14 (4.4 %) patients were confirmed as cryptococcosis. Based on molecular type, 85.7 and 14.3 % of the isolates were C. neoformans VN I and VN II, respectively. Phylogenetic analysis of URA5 gene sequences revealed clustering of VN I and VN II isolates into two distinct clades with a substantial difference within each molecular type. Voriconazole and 5-fluorocytosine, respectively, had the lowest (0.031 μg ml −1 ) and highest (8 µg ml −1 ) MICs. The epidemiological cutoff values (ECVs) for amphotericin B, fluconazole, voriconazole and 5-fluorocytosine encompassed ≥97 % of all 14 C . neoformans VN I species. However, according to the CLSI document M59, ECVs for itraconazole (7; 50 % of the isolates) and for posaconazole (1; 7.1 % of the isolate), were one log2 dilution higher than the wild type range. Combinations of amphotericin B with 5-fluorocytosine, amphotericin B with fluconazole and fluconazole with 5-fluorocytosine exhibited synergistic effects against 37, 31 and 12.5 % of the isolates, respectively. Conclusion. Our findings may significantly contribute to the development of management strategies for patients at a higher risk of cryptococcosis, particularly HIV-positive individuals.